Preparation and Characterization of Sodium Alginate/Chitosan Composite Nanoparticles Loaded with Chondroitin Sulfate - X. B. Yin; Q. Z. Yu; B. W. Li; C. D. Zhang (Advances in Materials Science and Engineering)
The chondroitin sulfate (CS)/sodium alginate (SA)/chitosan nanoparticles were prepared by electrostatic spraying technology. Laser particle size analyzer measurements indicated that the size of the particles is strongly affected by the weight ratio of raw materials, receiver rotation speed, injection rate, and so on. The size increased and size distribution moved towards the direction of large particle size with the decrease of applied voltage and increased with the increase of the flow rate and weight ratio of SA to CS; there is an optimal value for the effect of stirring rate on particle size and particle size distribution. The effect of different weight ratios of raw materials and pH on the sustained release rate of the product was investigated using a UV-visible spectrophotometer. Results showed the cumulative release rate of these particles was weight ratio of SA to CS and pH-dependent. The cumulative release rate of the CS/SA/chitosan composite nanoparticles with a weight ratio of SA to CS of 2 : 1 was higher at pH 6.8 than that at pH 1.2. By optimizing the process parameters, the CS/SA/chitosan composite particles were prepared, in which most of CS could pass through the stomach and release in the intestinal tract.